Performance of Broilers and Native Chickens Fed with Unfermented and Fermented Arenga Waste - Nurmi, Aisyah; Harahap, Nurainun; Santi, Melia Afnida (Indonesian Journal of Agricultural Research, 2018)
The objectives of this research were to study the performances of broilers and native chicken given arenga waste (APAF) fermentation by Saccaromyces cerevisiae and arenga waste unfermentation (APA) in the ration. Sixty day-old chicks of broiler Arbor Acres strain and sixty native chicken were divided into four dietary treatments and three replications (10 birds/replicate). Design of this experiment was completely randomized design factorial 2x2, with factor A was feeding (A1 = arenga waste unfermentation, A2 = arenga waste fermentation), and factor B was chickens type (B1=native chicken, B2=broilers). The variables observed were: daily weight gain, feed consumption, and feed conversion. The results showed that the performances of the broiler given fed with unfermented and fermented arenga waste showing no significant differences between all treatments. The results showed that there is an interaction between feeding and chicken type was no significant differences (P>0.05). Conclusion from this research of using fermented and unfermented arenga waste until level of 2.5% in ration showed no significant differences in the performance.